Peran Media Sosial Sebagai Upaya Promosi Kesehatan - Seri Wahyuni; Greiny Arisani; Riani Riani; Hanipah Hanipah (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2021)
Abstract – As information technology advances, the requirement for accurate and up-to-date health information grows. The worldwide efforts to promote health have demonstrated the significance of social media. As a result, the purpose of this study is to answer three questions: 1) the urgency of using social media in health promotion; 2) the type of social media used and its shortcomings; and 3) the role of health professionals in using social media to promote health. Search engine entries for international journals include Google Scholar, Sage Publications, and Othervier Publications. 35 journals on social media use, 33 journals on the characteristics of social media used and their weaknesses, and 17 journals on the role of health professionals in promoting health-based social media were selected from a search of 100 international publications. Social media have a positive impact on health promotion efforts, according to search results, but they also have some drawbacks, including: a lack of outreach to a passive audience, information that is false and inaccurate, a lack of interaction with the audience, and health professionals' limited capacity to use social media, which prevents program sustainability. Health professionals must incorporate social media into health communication and promotion strategies in order to create social media-based health promotion models.